MAINTENANCE OF MINANGKABAU CULTURE IN RANDAI AT MUNGKA BASED ON EDUCATION AND TOURISM - Maryelliwati, Maryelliwati; Rahmat, Wahyudi; Anwar, Khairil (Universitas Andalas, 2019)
Mungka District has a variety of traditional art forms that are still alive and growing. Silek or randai is not documented as a good medium, making it disappear from the community both old and young. Whereas the various forms of art in this case are the Minangkabau Silek as one of the main elements in Randai art, having local wisdom values but are less in demand, especially towards the younger generation. Therefore, documentation of retention of the Minangkabau silek in the traditional Randai arts is very necessary to maintain the existence of the art, as well as increasing the value of traditional and cultural tourism in West Sumatra because it can be re-broadcasted with various electronic media. Documenting the traditional art ofÂ Silek in Randai can be done by going directly to the field and introducing it to elementary schools as teaching material in the field ofÂ Natural Culture, Minangkabau. This study uses a qualitative method. The instruments to be used are observation, interviews, questionnaires, and direct observation, analysis, and writing of research results. From this documentation it was found that young people became interested again to reprint or reproduce the forms of documentation Silek in Randai to be used in the education world or traded as a cultural asset.